Intrigues behind the Harem Wall: Social, Cultural and Political Construction of Life behind the Harem of Sultan Sulaiman I - Eka Hendry Ar. (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
The urgency of exploring the history of the harem is important, not only because of being a rare phenomenon today or no longer in existence but perhaps this work is like opening the pandora’s box, a nightmare for women. This paper is presented as an academic review to portrait the fact that power is always in contact with wealth and attractive women, especially during a period when patriarchy was dominant. Sultan Sulaiman I was in power between 1520 to 1566 AD, in the 16th century AD. In western literature, Sultan Sulaiman was known as Suleyman the Magnificent. The work concludes, first, that the harem to the people of the Middle East in the medieval times was considered respectable for the family, especially for women both in the context of the imperial and domestic harem, where it was constructed in the name of honor, comfort and safety for women. Second, the construction of social, cultural and religious institutions of harem is the integration between the will to protect and maintain the honor of women, the concept of marriage in Islam and the patriarchal system hegemony in the Islamic world particularly in the context of the imperial harem. Third, the role of Sulaiman I who was “brave” to go against the tradition that had been practiced for many years in the Ottoman Empire, a milestone was important for the emancipation of women of the harem. Finally, to respond to the harem tradition, we must be in an impartial position, between the construction of the West and East.